INVESTIGATION OF STABLE MOVEMENT OF THE IMPROVED CHISEL CULTIVATOR AT THE SPECIFIED PROCESSING DEPTH - Mansurov Mukhtorjon Toxirjonovich; B.U.Toshpulatov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In order to improve the quality of work and reduce energy consumption, an analytical expression is given, taking into account the factors that affect the performance of the improved chisel cultivator at a certain depth of cultivation and stable movement at this depth. The analysis of the obtained expression showed that the operation of the improved chisel cultivator at a set depth and stable movement at this depth is mainly provided by changing the vertical distance N1 from its base plane to the lower hanging points.